2021
DOI: 10.3390/ijerph18115896
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Epinephrine Administered during Cardiopulmonary Resuscitation on Cerebral Oxygenation after Restoration of Spontaneous Circulation in a Swine Model with a Clinically Relevant Duration of Untreated Cardiac Arrest

Abstract: Severe neurological impairment was more prevalent in cardiac arrest survivors who were administered epinephrine than in those administered placebo in a randomized clinical trial; short-term reduction of brain tissue O2 tension (PbtO2) after epinephrine administration in swine following a short duration of untreated cardiac arrest has also been reported. We investigated the effects of epinephrine administered during cardiopulmonary resuscitation (CPR) on cerebral oxygenation after restoration of spontaneous cir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Here, 66.7% of the animals in the IT‐saline group experienced cerebral cortical hypoxia, although the MAP and Pa o 2 clearly remained within the normal range throughout the 5‐hour observation period; multiple studies have reported similar findings. 27 , 28 , 40 In a clinical study including 14 patients comatose following cardiac arrest who underwent multimodal neuromonitoring, 7 (50%) experienced PctO 2 <20 mm Hg. 40 Microcirculation is dissociated from macrovascular circulation during the early post‐ROSC period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, 66.7% of the animals in the IT‐saline group experienced cerebral cortical hypoxia, although the MAP and Pa o 2 clearly remained within the normal range throughout the 5‐hour observation period; multiple studies have reported similar findings. 27 , 28 , 40 In a clinical study including 14 patients comatose following cardiac arrest who underwent multimodal neuromonitoring, 7 (50%) experienced PctO 2 <20 mm Hg. 40 Microcirculation is dissociated from macrovascular circulation during the early post‐ROSC period.…”
Section: Discussionmentioning
confidence: 99%
“…The anesthesia, preparation, and data collection procedures have been previously described. 27 , 28 , 29 , 30 Briefly, following initial sedation with intramuscular administration of ketamine (20 mg/kg) and xylazine (2.2 mg/kg), the animals were tracheostomized and mechanically ventilated with a 70/30 mixture of N 2 O/O 2 and sevoflurane (titrated to maintain adequate anesthesia). An end‐tidal carbon dioxide sampling line was placed between the ventilator circuit and tracheal tube.…”
Section: Methodsmentioning
confidence: 99%
“…Postischemic cerebral hypoperfusion occurs within the first hour after ROSC and persists for at least several hours. 37 , 38 , 39 Therefore, it would be desirable to perform this treatment within the first hour after ROSC, preferably before or shortly after the onset of postischemic cerebral hypoperfusion, to minimize the detrimental effects of postischemic cerebral hypoperfusion. However, in real‐world clinical practice, it would be difficult to administer SNP intrathecally within the first few hours after ROSC as multiple life‐saving procedures, such as percutaneous coronary intervention, are performed during this period.…”
Section: Discussionmentioning
confidence: 99%